2015
DOI: 10.2166/wst.2015.586
|View full text |Cite
|
Sign up to set email alerts
|

Detection of semi-volatile organic compounds (SVOCs) in surface water, soil, and groundwater in a chemical industrial park in Eastern China

Abstract: China is suffering from serious water and soil pollution, especially in the North China Plain. This work investigated semi-volatile organic compounds (SVOCs) in surface water, groundwater and soil within a chemical industrial park in Eastern China, for which the volatile organic compound (VOC) results have been previously reported. A total of 20 samples were collected from the field, and analyzed in the laboratory. A 100% detection frequency of SVOCs in samples from this chemical industrial park was observed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…China is one of the largest producers and users of HCHs in the world and is also most seriously affected by HCHs pollution. Although HCHs were banned from production and utilization in China since 1983, due to their environmental persistence, they can still be detected in the atmosphere, surface water, groundwater and Molecules 2022, 27, 2874 2 of 11 soil [3][4][5][6][7]. Therefore, there is an urgent need to study the fate and environmental behavior of HCHs in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…China is one of the largest producers and users of HCHs in the world and is also most seriously affected by HCHs pollution. Although HCHs were banned from production and utilization in China since 1983, due to their environmental persistence, they can still be detected in the atmosphere, surface water, groundwater and Molecules 2022, 27, 2874 2 of 11 soil [3][4][5][6][7]. Therefore, there is an urgent need to study the fate and environmental behavior of HCHs in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Human activities in these regions have led to serious environmental problems, including groundwater contamination. Previously, we have published reports on volatile and semi‐volatile organic compounds (VOCs and SVOCs) detected in groundwater in China (Bi et al ; Chen et al ; Liu et al , ). Other researchers reported the detection of inorganic contaminants such as nitrate and heavy metals (Li et al ; Bai et al ; Chen et al ; Xi et al ).…”
Section: Introductionmentioning
confidence: 99%
“…[166] In addition, due to being semi-volatile, they are able to exist in the vapor phase of the atmosphere or be ad/ab-sorbed by atmospheric particles, thereby facilitating transport over long distances through the atmosphere. [189] In this study, different analytical methods including gas chromatography -mass spectrometry showed high domination of the most chlorinated compounds comparing to the less chlorinated ones. PCA analysis of factor loadings for every component extracted and compared to the work previously conducted in neighbouring countries showed possible contributions of the emissions from electronic waste (incineration plant in Tuas) [62] and ship-dismantling activities [146].…”
Section: Chapter 9 Summary and Conclusionmentioning
confidence: 63%
“…Among all 16 PAHs detected and quantified, the most abundant PAHs can be classified in two groups: NAPH and ACP (lighter PAHs) and BbF, BkF, BaP, IcP, DhA, BghiP (heavier PAHs). Dominance of this specific congeners suggests domestic heating and long term transport from neighbouring countries (India, Nepal, China) as a sources of the PAHs in this sampling site [156,161,189,208,220,228]. …”
mentioning
confidence: 80%
See 1 more Smart Citation